Method of making fluid-issuing openings through the walls of flexible plastic members, particularly dripper emitters - DRORI, MORDEKI (1980)
Described is a method of making fluid-issuing openings through the wall of flexible plastic members, particularly fluid conduits, by forming each opening through a small radius of curvature portion of the conduit wall while the respective wall portion is of curved oblong shape in cross-section, such that during use of the conduit, it assumes a circular shape, thereby increasing the radius of curvature of the wall portion and reducing the cross-sectional area of the outer part of the opening formed therethrough. The method is particularly described for producing linear-source water irrigation emitters which have a smaller sensitivity to clogging, which are easier to clean, and which have a smaller sensitivity to pressure variations in the water supply line.